Perkembangan Sosial Remaja Di Kampung Baru Kelurahan Indarung Kecamatan Lubuk Kilangan Padang Sumatera Barat - Fratiwi, Rahmi; Arief, Asmaiwaty; S, Gusneli (Bimbingan dan Konseling, 2014)
This research was based on violence phenomenon that happened adolescent in the Kampung Baru Kelurahan Indarung Kecamatan Lubuk Kilangan Padang, West Sumatera. The problem in my research is development of social adolescent. The goal of the research are to describe 1) The internal factor that influenced the development of social adolescent 2) external factor that influence the developement of the social adolescent. The kind of this research is included as qualitative descriptive that is character of a case study. The subject of this research consist of 3 tenagers who are about 14 until 17 years old in the Kampung Baru Kelurahan Indarung Kecamatan Lubuk Kilangan Padang, West Sumatera. While the addtional informers are twelve persons who can give the information about this reasearch which is researched by technical researcher that used in this research is snow ball technic. The results of the research show that the development of social adolescent in Kampung Baru Kelurahan IndarungÂ  Kecamatan Lubuk Kilangan Padang, West Sumatera have distruction of internal and external. The internal distruction of the adolesent are doing such presure to themselves and also hide themselves from social environment on where they live. In addition, the external distruction are some of them smocking, fighting and having authoritative or always want to hold the power.